The Correlation Between Topographic Characteristics and the Thickness, Elemental Accumulation of Ni, Fe, and MgO, as well as the Distribution Pattern of Laterite Deposits: Using the 2D Inverse Distance Weighting (IDW) Method in Wolo District, Kolaka Regency, Southeast Sulawesi Province - Rohaya Langkoke; Ilham Alimuddin; Meinarni Thamrin; Muhammad Mozart Suad (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The research area is administratively located within the PIT Z area of PT. Ceria Nugraha Indotama's mining permit (IUP) in Wolo District, Kolaka Regency, Southeast Sulawesi Province. This study examines the correlation between topographic features and laterite deposit characteristics in the study region. The research methodology incorporated fieldwork, data processing using ArcMap 10.8 and Surpac 6.3 software, and laboratory analyses including petrographic and geochemical examinations. Analysis revealed two primary topographic features in the research area: steep hills and undulating hills. Steep hill topography exhibited high concentrations of MgO compounds and relatively thin laterite deposits. Conversely, undulating hill topography demonstrated optimal laterite deposits characterized by thicker laterite horizons and elevated Fe and Ni content. The distribution pattern of laterite deposits throughout the study area indicates that slope gradient significantly influences water drainage, which serves as the principal medium for the lateritization process, thereby establishing a direct relationship between topographic features and laterite deposit profiles.